Influence of a strong beam on structure and properties of plasma coatings - S.A. Guchenko; E.N. Eremin; V.M. Yurov; V.Ch. Laurynas; S.S. Kasimov; O.N. Zavatskaya (Қарағанды университетінің хабаршысы. Физика сериясы)
The effect of electron irradiation on the structure and properties of plasma coatings is studied. The coatings were obtained by vacuum spraying of Fe-Al and 12X18H10T cathodes. The microstructure, microhardness and friction coefficients before and after irradiation by electrons were studied. After irradiation, all the characteristics of the coatings change. Taking into account the surface tension at the interface, leads to a significant change in the kinetics of the formation of coatings. The greater the surface tension, the lower the dissipation rate of the free energy. This means that most of the energy supplied goes to the formation of the coating. In this case, as a rule, cellular nanostructures with increased hardness are formed. Methods of determination are proposed and the melting and recrystallization temperatures of plasma coatings are estimated. It is established that the melting temperature of coatings obtained in argon is higher than for coatings obtained in a nitrogen medium. It was shown experimentally that 12X18H10T + Al, 12X18H10T + Fe-Al and 12X18H10T + Cu coatings obtained in argon medium have higher melting and recrystallization temperatures. This means that the latter can be used as a heat-resistant coating on steel parts. It is shown that the surface tension of coatings obtained in a nitrogen medium is lower than for coatings obtained in argon. Hence, the formation of nitride phases leads to a decrease in the surface energy of the coatings. It is shown that the greater the surface tension of the coating, the higher its corrosion resistance. It is established that the corrosion resistance of most of the coatings studied is not inferior to the most corrosion-resistant steels.